Clinical and pelvic floor ultrasound characteristics of pelvic organ prolapse recurrence after transvaginal mesh pelvic reconstruction - Zhenzhen Liu; Gaowa Sharen; Pan Wang; Liyuan Chen; Li Tan (BMC, 2022)
Abstract Background Recurrence of pelvic organ prolapse (POP) after transvaginal mesh (TVM) implantation pelvic floor reconstruction surgery remains an unresolved problem in clinical practice. In this retrospective observational study, clinical and pelvic floor ultrasound (PFUS) parameters were analyzed in order to identify high-risk factors of POP recurrence. Methods The clinical and PFUS data from September 2013 to November 2019 of patients who underwent TVM were retrospectively analyzed. The patients with prolapse recurrence on postoperative follow-up diagnosed by PFUS were selected as case group, the clinical and PFUS parameters of them were compared with the control group in which the patients had no sign of prolapse recurrence. Univariate and multivariate regression analyses were performed based on age, BMI, gravidity, parity, surgical history (non-POP hysterectomy and incontinence-or-POP surgery), preoperative POP stage, follow-up in years, levator avulsion and hiatal area (HA) on Valsalva. Results Altogether 102 patients entered the study and the median interval between PFUS and TVM surgery was 2.5 years. Univariate analysis showed that levator avulsion and HA were significantly different between case group and control; multivariate regression analysis showed that only HA was related to prolapse recurrence after TVM (OR = 1.202, 95% CI 1.100-1.313, P < 0.001). The area under the ROC curve was 0.775 (95% CI 0.684-0.867, P < 0.001). Conclusions Hiatal area on Valsalva was related to prolapse recurrence after TVM surgery and it is an important parameter for postoperative follow-up of TVM surgery.